Cardiovascular Disease in Women with Chronic Renal Failure (Journal of Medicine, 2015)
Objective: Patients with chronic renal failure have high burden of cardiovascular morbidity and mortality. This study was carried out to investigate the development of cardiovascular disease in chronic renal failure among female patients on dialysis treatment in Nigeria. Materials and Methods: A total of 40 adult female subjects participated in this study. 20 of them were apparently healthy and served as control group while the rest 20 were female patients with chronic renal failure (CRF) on dialysis treatment. Fasting blood samples were collected and their lipid profile, Total Cholesterol (TC), Triglyceride (TG), High Density Lipoprotein Cholesterol (HDL-C), Low Density Lipoprotein Cholesterol (LDL-C), and Very Low Density Lipoprotein Cholesterol (VLDL-C) were estimated using enzymatic methods. The percentages of these parameters in circulation were obtained. The cardiovascular risk ratios (TC/HDL-C and LDL-C/HDL-C) were calculated. Result: The lipid profile of the chronic renal failure patients (TC 5.70±0.80mmol/l, TG 1.46±0.40mmol/l, LDL-C 3.50±0.2mmol/l, and VLDL-C 0.67±0.2mmol/l) were significantly higher (p